A Unique Presentation of Meibomian Gland Carcinoma - Ashish Kumar Pandey; Anirudh Singh; Mansur Ali Khan; Anjali Maheshwari (Delhi Journal of Ophthalmology)
Background:- The sebaceous gland carcinoma is a lethal highly malignant slow-growing tumor of the eyelid arising from meibomian glands, glands of Zeis, sebaceous glands of caruncle, and periocular skin. It is third most common malignancy of the eyelid and the incidence rate is about 1-1.5%.1 We report a unique case of meibomian gland carcinoma which was a diagnostic challenge due to its unusual presentation. Case Report 62 year old male presented with solitary painless slowly growing mass left upper eyelid of 6 months duration. Incisional biopsy revealed basal cell carcinoma. Wide local excision was performed and defect closed with primary suturing. Biopsy of the mass revealed meibomian gland carcinoma with positive medial and lateral margins. Second surgery was performed in which wider local excision was done including medial canthus. Defect of 3.5 cm was closed with Tenzelʼs flap. Conclusion: The case is being reported for highlighting the unusual presentation of the meibomian gland carcinoma as a slow growing swelling and confusing nature of the histopathology reports.